Quality of Service in mobile ad hoc networks - Soufy, Khaled Abdullah Mohammed Al (2013)
To support multimedia applications, it is desirable that an ad hoc network has a provision of Quality of Service (QoS). However, the provision of QoS in an ad hoc network is a challenging task due to its inherent characteristics. In this thesis, our main focus is on the provision of QoS in an ad hoc network where there can be multiple hops from a given source to a destination.